INJURIES IN ELITE U18 FIELD HOCKEY PLAYERS AT A MAJOR TOURNAMENT. Issue 4 (1st February 2017) - Furlong, Laura-Anne; Rolle, Udo
Abstract : Background: There is little data on injuries in elite U18 field hockey players, which limits development of appropriate evidence-based injury prevention strategies. Objective: Quantify incidence and characteristics of injuries in elite U18 field hockey players at a major tournament. Design: Prospective injury surveillance. Setting: 2016 EuroHockey Youth Championships, Ireland. Participants: Sixteen national representative teams; 8 in each of the boys and girls competitions. Main Outcome Measurements: Number of, type, mechanism and site of injuries occurring on the pitch where play was stopped for the player to receive attention. Results: Across the six-day tournament, 39 injuries were reported (20 in boys competition, 19 in girls; average: 0.98 injuries per match). In the boys competition, fifteen contusions were observed primarily due to being hit by the ball/stick, with fractures (2), being winded (2) and sprains (1) also reported. Most injuries (15) occurred in the lower limb or torso, with three in the upper limb and two to the head/face where players collided with each other. Three injuries occurred when struck by the ball defending penalty corners, resulting in two lower limb contusions and one fractured finger. In the girls competition, 10 of 19 injuries were contusions, also primarily due to being hit by the ball/stick. Sprains (3), lacerations (2), being winded (2), strains (1) and cramp (1) were also reported. Ten occurred in the lower limb, five to the head/face (four due to being hit by the stick), one to the upper limb and three to the torso. Two injuries occurred defending penalty corners, resulting in contusions to the thigh and hand. Conclusions: Injury incidence in elite U18 field hockey is low but the high number of injuries due to being struck by the ball or stick highlights the importance of design and use of appropriate protective equipment for youth athletes.